PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN MANUFAKTUR - RHETNO WULANSARI; ANDRY IRWANTO (Jurnal Ekonomi dan Bisnis Airlangga, 2018)
Introduction: This study aims to determine the effect of insider ownership, audit committees, leverage, firm size, the number of independent commissioner on the performance of manufacturing firms in the Indonesian stock exchange. Methods: The type of data used in this research is quantitative data. This study uses a tool to answer the hypothesis in the form of multiple linear regression. The number of samples taken by the sampling technique as many as 50 companies listed in Indonesia Stock Exchange. Results: From the test results indicate that there is insider ownership, audit committees, leverage significant positive effect on the performance of manufacturing companies in Indonesia Stock Exchange. firm size and the number of independent commissioners no significant positive effect on the performance of manufacturing companies in Indonesia Stock Exchange. Conclusion and suggestion: The implication of these findings is that insider ownership, audit committees, and leverage it will be able to produce a good performance. Although firm size and the number of independent commissioners has no effect, but still must be considered, because if the firm size and the number of independent commissioners are not in accordance with the provisions of SFAS may result in the presence of certain interests that are not in accordance with the company's goals.